COMPARATIVE ANALYSIS OF PROPER MOTIONS OF STARS IN OPEN CLUSTERS BY USING VO TOOLS - Mazhaev, A.; Protsyuk, Yu. (Одеські астрономічні публікації, 2014)
Astrometric catalogues such as Tycho2, Mobitel1, CSOCA, XPM, PM2000, SDSS-DR9 were used for cross identification of stars, visualization of proper motions and further data processing by using available Virtual Observatory (VO) Tools: cross-match service (CDS,Strasbourg), TopCat, Aladin. The coefficients of linear correlation for common stars as well as the standard deviations for differences of proper motions were determined for at least ten pairs of catalogues to compare the accidental errors and the systematic biases between the given data sets.